Breast Cancer Interaction Network Concept from Mostly Related Components: - Zamanian Azodi, Mona; Rezaei-Tavirani, Mostafa; Bashash, Davood; Ahmadi, Naybali; Rostaim-Nejad, Mohammad (Galen Medical Journal, 2019)
Background: Management of breast cancer (BC) as a heterogeneous disease is very challenging. Biomarker discovery has been shown promising for this aim. Protein interaction mapping could provide further knowledge of the vital roles of these markers. Materials and Methods: Cytoscape and its plug-ins are used for network construction and evaluation. The plug-ins used in this study are STRING, Network Analyzer, GeneMANIA, and CluePedia. Results: The central proteins are enriched in transcription regulatory region DNA binding, regulatory region nucleic acid binding, regulatory region DNA binding, Fc receptor signaling pathway, cell cycle arrest, and immune response-regulating cell surface receptor signaling pathway. Conclusion: The introduced biomarkers and their related biological processes may show useful for the breast cancer diagnosis and monitoring; however, has to encounter more validation studies to be clinically applicable. [GMJ.2019;8:e1298] Â 